Perancangan Sistem Keamanan Brankas Menggunakan Metode Finger Print Berbasis SMS Gateway - Sri Watmah; Hanggoro Aji Al Kautsar; Suryanto Suryanto (LPPM Universitas Bina Sarana Informatika, 2021)
Abstract - For some people or companies need a means of storing valuables from the danger of theft / demolition. Tools commonly used to store valuables are usually in the form of a safe. Safe is a cupboard or metal box that is used to store valuables. Even though it is made of iron and has a special lock, the safe still needs to use technology for its security. Especially now that theft is rampant. As a solution to this problem, an integrated technology for storing valuables is needed. In this study, the authors create a safe security system using a finger print method based on sms gateway. With the implementation of a dual security system, namely with fingerprints as access to open doors and notifications via email if it is not the owner who opens access to the safe. Fingerprints that can be used to access the safe door are only fingerprints that have been recorded into the safe user system while the power or voltage used in this security uses 9 Volts, namely using a 9 Volt adapter. Keywords: Brankas, SMS gateway, finger print.